(untitled) (Annals of Medical Research, 2021)
Aim: Breast cancer continues to be the most common type of cancer among women. Recent development in epigenomics has highlighted key mechanisms in which epigenetic regulation contributes to cancer treatment. Epigenetic modulating drugs promises novel approaches targeting cancer treatment. Belinostat is a histone deacetylase inhibitor approved by the U.S. Food and Drug Administration (FDA) in 2014 for the T-cell lymphoma. This study aimed to investigate the apoptotic effects of Belinostat on MCF-7 cells. Materials and Methods: For this purpose, The IC50 value of Belinostat was determined by XTT assay and the apoptotic effect of Belinostat on MCF-7 cells was evaluated. Expression of apoptosis-related genes including Caspase 3 (CASP3), CASP9, apoptotic protease activating factor-1 (APAF-1) and tumor protein P53 (P53) were evaluated by quantitative Real-Time PCR.Results: The IC50 dose of Belinostat was determined as 5 μM for 48 h. The results of study showed that Belinostat administration decreased the number of cancer cells in the MCF-7 cell population and down regulated the gene expression of apoptosis-related genes.Conclusion: Results indicated that Belinostat, can be considered as an option in the treatment of breast cancer. It is considered that it would be more beneficial to perform more sophisticated in vivo and in vitro studies about apoptotic effect of Belinostat.